Computational study of the ro-vibrational spectrum of CO–CO2 - Castro-Juárez, Eduardo; Wang, Xiao-Gang; Carrington, Tucker; Quintas-Sánchez, Ernesto; Dawes, Richard (The Journal of chemical physics, 2019)
An accurate ab initio ground-state intermolecular potential energy surface (PES) was determined for the CO–CO2 van der Waals dimer. The Lanczos algorithm was used to compute rovibrational energies on this PES. For both the C-in and O-in T-shaped isomers, the fundamental transition frequencies agree well with previous experimental results. We confirm that the in-plane states previously observed are geared states. In addition, we have computed and assigned many other vibrational states. The rotational constants we determine from J = 1 energy levels agree well with their experimental counterparts. Planar and out-of-plane cuts of some of the wavefunctions we compute are quite different, indicating strong coupling between the bend and torsional modes. Because the stable isomers are T-shaped, vibration along the out-of-plane coordinates is very floppy. In CO–CO2, when the molecule is out-of-plane, interconversion of the isomers is possible, but the barrier height is higher than the in-plane geared barrier height.